The Menace of inflation : a symposium - Wiegand, G. Carl.; Committee for Monetary Research and Education; Georgetown University (Old Greenwich, Conn. : Devin-Adair Co., 1977)
In the book, sixteen major business writers, economists and political figures explore the causes and consequences of continuing inflation and suggest some unconventional solutions, many of which are certain to stir up controversy
Essays delivered at a conference of the Committee for Monetary Research and Education at the Center for Strategic and International Studies, Georgetown University, Washington, D.C., Nov., 1974.
osc 08/08/2018
Loans
Keywords: Inflation (Finance); Inflation (Finance)